Evaluation of a Combination Rapid Immunoassay for Detection of Giardia and Cryptosporidium Antigens - Chan, Raymond (American Society for Microbiology, 2000)
A combination cassette format nonenzymatic rapid immunoassay for detection of Giardia and Cryptosporidium antigens was evaluated by using 556 patient stool specimens from three clinical laboratories. This assay (Genzyme Diagnostics Contrast Giardia/Cryptosporidium), which can be used with fresh or formalin-fixed specimens, had unadjusted sensitivities and specificities of 96.1 and 98.5% for Giardia and 100 and 98.7% for Cryptosporidium, respectively, in this study.